Disfunción familiar en adolescentes de quinto de secundaria de un Colegio público y un Colegio privado en el distrito de La Molina - Escobar Sáez, María Jesús (2015)
The research was aimed to analyze the differences in the level of family dysfunction in adolescents in senior year in both a private and a public school in the district of La Molina. Also, to determine if there are differences according to gender, the presence of parents in the home in the levels of dysfunction. The sample consisted of 214 students between 15 and 19 years old, 106 of them were from a public school and 107 from a private one. Family Dysfunction Inventory (IDF) was used to determine the level of family dysfunction. The results showed that there are significant differences in the level of dysfunction according to the school of origin and by gender, however, no difference was found for the presence of one or both of the parents at home.